2005
DOI: 10.1016/j.otohns.2004.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Elective neck dissection versus observation in primary parotid carcinoma

Abstract: The diagnosis of malignancy was known preoperatively in 59 (71%) cases, the exact histologic tumor type in 36 (43%) and the grade in 37 (44%) of 83 cases. Occult metastases were detected in 8 (20%) of 41 cNO patients, in 5 cases associated with a high-grade and in 3 cases with a low-grade carcinoma. Recurrence of disease developed in 5 (12%) patients in the elective neck dissection group and in 11 (26%) patients in the observation group. All of the 7 neck recurrences occurred in the observation group. The 5-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 22 publications
4
97
0
3
Order By: Relevance
“…This is encouraged by a study of 168 primary parotid gland malignancies, in which Walvekar et al [19] could show that of low-risk histology patients who underwent neck dissection 40% had pN+ disease. Furthermore, comparing elective neck dissection versus observing in high-and low-grade primary parotid gland carcinoma, Zbaren et al [20] conclude that a routine elective neck dissection is suggested in all patients with primary carcinoma of the parotid gland. The occurrence of intraparotideal metastases in cN¡/pN+ patients was 70.0%.…”
Section: Discussionmentioning
confidence: 99%
“…This is encouraged by a study of 168 primary parotid gland malignancies, in which Walvekar et al [19] could show that of low-risk histology patients who underwent neck dissection 40% had pN+ disease. Furthermore, comparing elective neck dissection versus observing in high-and low-grade primary parotid gland carcinoma, Zbaren et al [20] conclude that a routine elective neck dissection is suggested in all patients with primary carcinoma of the parotid gland. The occurrence of intraparotideal metastases in cN¡/pN+ patients was 70.0%.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of occult metastasis in elective neck dissection (END) specimens has been reported to be between 20 and 37% [34,35] . Thus, the performing of END for all cN0 parotid cancers implies that more than half of patients are over-treated.…”
Section: Sentinel Node Biopsy In Primary Parotid Cancermentioning
confidence: 99%
“…The overall incidence of LN metastases at presentation for primary parotid carcinomas in all age groups ranges between 18 and 28 % [67,68]. In the adult literature, recommendations range from routine elective neck dissection in all patients with primary carcinoma of the parotid gland [67] to neck dissection under specific circumstances including patients with tumors larger than 3 cm, high-grade tumors, facial paralysis, extra-glandular extension, and perilymphatic invasion [69]. Others argue in support of a supra-omohyoid neck dissection in patients with high-grade tumors for staging purposes, reserving an elective full neck dissection for patients with undifferentiated and squamous cell carcinomas [70].…”
Section: Surgerymentioning
confidence: 99%